Modeling and simulation of logistic processes: risk assessment with a fuzzy logic technique. (June 2018) - Gajović, Vladimir; Kerkez, Marija; Kočović, Jelena
Logistic processes imply the presence of a large number of different types of risks, primarily in the fields of transport, transshipment, and storage of goods. The main reason for this fact is the presence of numerous participants of logistic systems, the existence of various interactions between large numbers of subsystems or subprocesses, which causes disturbances and uncertainties, both locally and at the system level. The initial idea of this research is to model the total risk of logistic processes based on evaluation of the significance of different risk elements, their interrelations, and their influence on total risk. This paper presents a developed fuzzy logic model based on the analytic hierarchy process (AHP) model and fuzzy analytic hierarchy process (FAHP). The model is designed to be practical, understandable, and easy to implement and maintain. The incorporated data have different forms of crisp numbers, triangular fuzzy numbers, and linguistic variables. Logistic process data are incorporated into the proposed model and validated with an example case.